Efficiency and hospital effectiveness in improving Hospital Consumer Assessment of Healthcare Providers and Systems ratings. Issue 4 (October 2016) - Al-Amin, Mona; Makarem, Suzanne C.; Rosko, Michael
Abstract : Background: Efficiency has emerged as a central goal to the operations of health care organizations. There are two competing perspectives on the relationship between efficiency and organizational performance. Some argue that organizational slack is a waste and that efficiency contributes to organizational performance, whereas others maintain that slack acts as a buffer, allowing organizations to adapt to environmental demands and contributing to organizational performance. Purposes: As value-based purchasing becomes more prevalent, health care organizations are incented to become more efficient and, at the same time, improve their patients' experiences and outcomes. Unused slack resources might facilitate the timely implementation of these improvements. Building on previous research on organizational slack and inertia, we test whether efficiency and other organizational factors predict organizational effectiveness in improving Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) ratings. Methodology: We rely on data from the American Hospital Association and HCAHPS. We estimate hospital cost-efficiency by Stochastic Frontier Analysis and use regression analysis to determine whether efficiency, competition, hospital size, and other organizational factors are significant predictors of hospital effectiveness. Findings: Our findings indicate that efficiency and hospital size have a significant negative association with organizational ability to improve HCAHPS ratings. Practice Implications: Although achieving organizational efficiency is necessary for health care organizations, given the changes that are currently occurring in the U.S. health care system, it is important for health care managers to maintain a certain level of slack to respond to environmental demands and have the resources needed to improve their performance.